Desenvolvimento de metodologia espectrofotométrica como alternativa para determinação do ácido 5-aminosalicílico em medicamentos - Corrêa, André Coradini (2018)
The development of new analytical methodologies is essential to create alternatives to the methods described in the pharmacopoeias, either for identification or quantification of drugs. The literature shows few methods of quantification of 5-aminosalicylic acid (5-ASA) in pharmaceutical forms, being the methodology most used by CLAE (High Performance Liquid Chromatography), which makes the procedure expensive and even unviable in certain sectors. Thus, it is justified the research by fast, efficient and low-cost methods for the analysis of this drug. This dissertation aimed to use the spectrophotometry technique for the determination of 5-aminosalicylic acid in different pharmaceutical forms, based on the formation reaction of a colored complex formed between 5-ASA and Fe3+ ions, which is known as the Trinder. Chapter 1 of this dissertation describes the methodology developed, as well as the results of this research, together with the relevant discussions. Experimental design (ED) and response surface methodology (RSM) were carried out in order to reduce the number of experiments and achieve the best conditions for complex absorbance procedure. Three factors at two levels were studied: 5-ASA concentration (150 mg/L; 275 mg/L and 400 mg/L), FeCl3 concentration (100 mg/L; 200 mg/L and 300 mg/L) and volume ratio (1:2; 1:1 and 2:1) between the amounts of 5-ASA and FeCl3. The developed method showed satisfactory values for linearity, precision and accuracy. The different drug formulations containing 5-ASA presented values that were in agreement with those specifications in the package. This spectrophotometric methodology proved to be low-cost, simple and fast to determine 5-ASA in pharmaceutical formulations.